Abstract Keyword Searching with Knuth Morris Pratt Algorithm - Ependi, Usman; Oktaviani, Nia (Scientific Journal of Informatics, 2017)
This research was conducted to answer the problems of researchers for finding publication or papers that suitable with their topics. In this research was developed software for searching abstract keyword using Knuth Morris Pratt algorithm to answer the problems of researchers. Waterfall model used to develop abstract keywords searching software as tools development that has five phases, namely communication, planning, modeling, construction and deployment. The software was developed can display search results effectively and efficiently according to the enter search keywords, it can see while search results are shown is in case sensitive. The software is also tested; the testing process is conducted by functional observation with black box testing approach, Observation results while testing is conducted show the software running suitable with expected or 100% same with entered keyword, so worthy to be used as one of the tools of researchers searching articles.